FACTORS OF CARIES DEVELOPMENT IN YOUNG CHILDREN - Yuldasheva F. U.; Niyazova O. A. (The Conference Hub, 2025)
According to recent studies, there is a tendency to increase the prevalence and intensity of dental caries in children. Dental caries is still the most common chronic disease among children. In the classical sense, dental caries is a chronic infectious disease induced by a violation of diet. The main "players" in the etiology of the disease are: cariogenic microorganisms, the substrate in the form of incoming carbohydrates, the host (body resistance and tooth enamel).